Nanostructures and properties of an Oxisol under no-tillage and mechanical chiseling (Research, Society and Development, 2021)
Soil compaction in no-tillage systems (NTS) affects the sustainability of this management. To overcome the problem, mechanical chiseling and maintenance of the vegetation cover suggested were as management practices in order toreestablish ideal cultivation conditions. The soil studied was occupied for 20 years with annual crops in conventional tillage system (plowing and leveling harrow). After, the NTS was implemented for 15 years old. In 2012, management were implemented to study the effects on soil quality, with mechanical chiseling, cover crops, rice and bean. Thepurpose of this study was to evaluate the effect of soil chiseling and the use of cover crops on the maintenance of NTS sustainability after a crop succession of rice and common bean on a clayed Orthic Ferralsol. After four years we evaluation were then carried out to analyze the effects of the system on the soil quality physical and chemical attributes. We studied five cover plants (Crotalaria juncea; Cajanus cajan; Pennisetum glaucum; Urochloa ruziziensis and Fallow) all in NTS with and without chiseling. In addition, we studied a natural Savannah fragment too. Chiseling with cultivation of Crotalaria juncea as vegetation cover improved the physical properties compared with the initial conditions. However, cover crops grown on unchiseled soil resulted in an increase in the chemical properties P, K, and Mg concentrations, pH, and soil organic matter. The soil nanostructures morphological characteristics is a promising indicator it quality, complementary to the chemical indicators, for being sensitive enough for the short-term detection of changes soil properties.